Composite indices of femoral neck strength in adult female soccer players - El Hage, R. (Journal of Clinical Densitometry, 2014)
The incidence of hip fractures increases with age in women. Hip fractures are associated with high morbidity and mortality rates. Hernandez et al suggested that peak bone mineral density (BMD) attained at the third decade may be the single most important factor for the prevention of osteoporosis later in life. Peak BMD is influenced by several factors such as genetics, nutrition, hormones, ethnicity, and mechanical factors. Mechanical loading is well known to stimulate bone formation and increase BMD.